La impugnación del reconocimiento de paternidad y el principio del interés superior del niño - Arandia-Zambrano, Juan Carlos; Rivera-Velasco, Luis Antonio; Zapata-Jaramillo, Nancy Cecilia (IUSTITIA SOCIALIS, 2021)
La impugnación del reconocimiento de paternidad y el principio del interés superior del niño